Virtual Brand Community in creating the Electronic Word of Mouth - Lisnawati, Lisnawati; Hurriyati, Ratih; Maulidyna, Risna (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2020)
The purpose of this research is to find the influence of virtual brand communities on electronic word of mouth on members of the Fortuner (ID42NER) car user community. A total of 95 respondents were using probability sampling. A questionnaire was used as a research instrument to collect data from respondents. The analysis technique used is verification technique using path. The research showed that the virtual brand community has an influence on electronic word of mouth.